Viabilidade técnica e potencial de redução de custo com utilização da casca do café como combustível alternativo na indústria cimenteira - Verdiani, Vicente Bueno (2024)
The ability to use coffee husk biomass as a source of renewable energy in co-processing for the manufacture of clinker was studied, with its effects on the cement product and its potential for reducing fuel costs and CO2 emissions. Coffee husks are a by-product resulting from the dry processing of coffee fruit, with 1kg of husk being generated for every 1kg of fruit processed. Brazil is the largest global coffee producer with a harvest, in 2022, of 3.17 million tons. Tests were carried out to characterize the coffee husk as an alternative fuel to replace petroleum coke for use in the pre-calciner (cyclone tower). For the study, the following tests were realized: granulometry, immediate analysis, dry and wet base humidity, lower and higher heating value, chloride content, apparent density, thermogravimetry, x-ray fluorescence spectrometry, potential cost reduction in replacing the coke by biomass, potential reduction in CO2 emissions when replacing to validate its use in co-processing. The results obtained showed that this biomass can be used, as it has a lower heating value of 3498 kcal/kg and the residues present in the ash, resulting from burning, do not impact the quality of the cement produced. In the analysis of the potential for reducing fuel costs, carried out with a 15% replacement of coke by biomass, an estimated reduction of R$ 6.06 million/year was obtained. Estimates of the potential for reducing CO2 emissions in the process indicate a reduction of 1.6 tons of CO2 for each ton of coke replaced.